Perkembangan Aspek Hukum Alih Teknologi Di Indonesia - Reinardus Budi Prasetiyo (Fakultas Hukum Universitas Bangka Belitung, 2020)
This legal research aims to analyze the various applicable laws and regulations related to the rules on technology transfer in Indonesia. The legal research method used in this legal research uses normative legal research and uses secondary legal material as a reference for collecting data. This legal research would like to convey the need for regulation of Sui Generis technology transfer which has become an interesting old issue and needs to be discussed. That the rules of technology transfer which are spread in various laws and regulations are felt to be unable to provide legal protection for the host country where developed countries invest and establish their companies. Inability to provide protection is basically no strict sanctions if the country or TNC does not make efforts to transfer technology as mandated by the legislation. This because the provisions regarding transfer technology are an agreement and do not have compelling power for developed countries or transnational companies. Therefore, by doing the preparation of technology transfer sui generis as well as special attention from the government about this condition, it will provide benefits and advantages for the host country to manage the transfer of technology that it obtains